2012
DOI: 10.1055/s-0032-1315363
|View full text |Cite
|
Sign up to set email alerts
|

Behandlungsergebnisse operativ versorgter kindlicher suprakondylärer Humerusfrakturen

Abstract: Regarding bony healing in all patients, well manageable complications, mostly excellent or good results in the MEPS and good function, crossed K-wire pinning after closed/open reduction is a safe standard surgical procedure for this type of fracture.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…A study by Ulmar et al showed excellent results in 46 patients (>90 points as per Mayo elbow grading) which was parallel to our study. 16…”
Section: Mayo Elbow Scorementioning
confidence: 99%
“…A study by Ulmar et al showed excellent results in 46 patients (>90 points as per Mayo elbow grading) which was parallel to our study. 16…”
Section: Mayo Elbow Scorementioning
confidence: 99%